Validation of the Modified Shuttle Test to Predict Peak Oxygen Uptake in Youth Asthma Patients Under Regular Treatment - Lanza, Fernanda C.; Reimberg, Mariana M.; Ritti-Dias, Raphael; Scalco, Rebeca S.; Wandalsen, Gustavo F.; Sole, Dirceu; van Brussel, Marco; Hulzebos, H. J.; Dal Corso, Simone; Takken, Tim (Frontiers in Physiology, 2018)
Background: Oxygen uptake (VO2) evaluations by cardiopulmonary exercise test is expensive and time-consuming. Estimating VO2 based on a field test would be an alternative. Objective: To develop and validate an equation to predict VO2peak based on the modified shuttle test. Methods: Cross sectional study, with 97 children and adolescents with asthma. Participants were divided in two groups: the equation group (EG), to construct the equation model of VO2peak, and the cross-validation group (VG). Each subject performed the modified shuttle test twice using a portable gas analyzer. The peak VO2peak during modified shuttle test was used in the equation model. The patients’ height, weight, gender, and distance walked during modified shuttle test were tested as independent variables. Results: The final model [-0.457 + (gender × 0.139) + (weight × 0.025) + (DW × 0.002)] explained 87% of VO2peak variation. The VO2peak predicted was similar to VO2peak measured by gas analyzer (1.9  0.5 L/min and 2.0  0.5 L/min, respectively) (p = 0.67), and presented significant ICC 0.91 (IC95% 0.77–0.96); p < 0.001. The Bland-Altman analysis showed low bias (-0.15 L/min) and limits of agreement (-0.65–0.35 L/min). There was no difference in DW between EG (760  209m) and VG (731  180m), p = 0.51. Conclusion: The developed equation adequately predicts VO2peak in pediatric patients with asthma.